'On the outside I'm smiling but inside I'm crying': communication successes and challenges for undergraduate academic writing. Issue 9 (21st October 2019) - Elliott, Samantha; Hendry, Helen; Ayres, Chloe; Blackman, Kim; Browning, Francesca; Colebrook, Daisy; Cook, Colin; Coy, Nathan; Hughes, Jessica; Lilley, Natasha; Newboult, Devon; Uche, Oluchi; et al.
Abstract: Student difficulties with the transition to writing in higher education are well documented whether from a 'study skills', an 'academic socialisation' or an 'academic literacies' perspective. In order to more closely examine the challenges faced by students from widening participation backgrounds and diverse routes into undergraduate study, this project focuses on first-year undergraduate experiences of developing academic literacies on an Education Studies programme at one university in England. It highlights the impact of different support and guidance within and beyond their degree programme where attempts to embed academic literacy development are part of subject modules. The paper reports the findings generated using a mixed methods interpretive approach. Questionnaires were collected at the beginning (n = 48) and end of the students' first year (n = 44), and interviews and visual data collection methods (n =19) were used at the mid-point of the academic year. Key findings highlight students' expectations of achievement on entry to university and the influence of the emotional journey of students as they begin to make progress as academic writers. Identifying, selecting and applying academic reading were an enduring concern whilst some students struggled with the digital literacy implicit in undergraduate work. Importantly, some strategies developed to support student transition to academic writing in higher education may have unintended consequences as they progress through the first year.